Concurrent validity of the ActiGraph GT3X+ and activPAL for assessing sedentary behaviour in 2–3-year-old children under free-living conditions. Issue 2 (February 2020) - Pereira, João R.; Sousa-Sá, Eduarda; Zhang, Zhiguang; Cliff, Dylan P.; Santos, Rute
Abstract: Objectives: ActiGraph accelerometer cut-points are commonly used to classify sedentary behaviour (SB) in young children. However, they vary from 5counts/5 s to 301counts/15 s, resulting in different estimates and inconsistent findings. The aim was to examine the concurrent validity of ActiGraph GT3X + cut-points against the activPAL for measuring SB in 2–3-year-olds during free-living conditions. Design: Observational validation-study. Methods: Sixty children were fitted with the activPAL and ActiGraph simultaneously for at least 2 h. Nine ActiGraph cut-points ranging from 60 to 1488 counts per minute were used to derive SB. Bland & Altman plots and equivalent tests were performed to assess agreement between methods. Results: Estimates of SB according to the different ActiGraph cut-points were not within the activPAL ±10% equivalent interval (-4.05; 4.05%). The ActiGraph cut-points that showed the lower bias were 48counts/15 s (equivalence lower limit: p  =  0.597; equivalence upper limit: p  < 0.001; bias: -4.46%; limits of agreement [LoA]: -21.07 to 30.00%) and 5counts/5s (equivalence lower limit: p  < 0.001; equivalence upper limit: p  =  0.737; bias: -5.11%; LoA: 30.43 to 20.20%). For the 25counts/15s, 37counts/15s and 48counts/15s ActiGraph cut-points, the upper limits were within the equivalent interval ( p  < 0.001) but not the lower limits ( p  > 0.05). When using the 5counts/5s and 181counts/15s ActiGraph cut-points, lower limits were within the equivalent interval ( p  < 0.001) but not the upper limits ( p  > 0.05). Confidence intervals of the remaining ActiGraph cut-points lie outside the equivalent interval. Conclusions: Although none of the ActiGraph cut-points provided estimates of SB that were equivalent to activPAL; estimates from 48counts/15 s and 5counts/5 s displayed the smallest mean bias (˜5%).